Parliamentary Procedure: Preparing Minutes of a Meeting - James E. Dyer (EDIS)
An official copy of the minutes of a meeting should be kept in a manner that is accessible to the membership, yet preserves their integrity as a historical record of the organization. This 4-page fact sheet was written by James E. Dyer and published by the UF Department of Agricultural Education and Communication, January 2013.